Changing the peritoneal dialysis access algorithm with a precise technique of percutaneous Seldinger PD catheter placement. Issue 4 (July 2022) - Swinnen, Jan "John"; Baker, Luke; Burgess, David; Allen, Richard; O'Grady, Allan; Chau, Katrina
Background: In 1953, Swedish radiologist Sven Seldinger introduced a technique for blood vessel or hollow organ access using a needle, guide wire and catheter. Over the last two decades, this technique has been used for Peritoneal Dialysis (PD) catheter placement, "Seldinger PD" (SPD). To improve the safety and accuracy of SPD, ultrasound, X-ray guidance, contrast imaging and micropuncture techniques have been incorporated to a greater or lesser extent. Methods: This manuscript describes a new and rigorous technique of SPD developed at our unit and results in the first 64 cases. One of our goals was to replace emergency Central Vein Catheter Hemodialysis with "Urgent-Start" PD. We therefore sought to develop a procedure that was ultra-safe, minimally invasive and readily done on the sickest patients under Local Anesthetic. As the technique was new to our unit, and because of progressive modifications of the technique, some of the results reflect our "learning curve." In addition, 55% of the patients referred to our program had "crashed" into renal failure, 32% were deemed "unfit for General Anaesthesia" by the Anaesthetists and 53% were moderately to severely obese, resulting in a very morbid and vulnerable cohort. Results: Despite this, we had no procedure related mortality, no organ injury and no significant bleeding. Technical success was 97% (intention-to-treat). Urgent Start PD was used in 36%; overall, 3/61 catheters placed experienced PD fluid leak. Correct catheter tip placement – in the Pelvic Pouch – was documented in all cases; significant catheter migration was seen in 18% of those with imaging follow-up, only two requiring revision. Most catheter migrations occurred early in our series before our low peritoneal puncture technique became standard. Conclusions: We believe this SPD technique is safe, precise, clinically and financially cost-effective and can replace other forms of PD placement in most situations.